REGIONAL ORGANIZATIONS AND SUPRANATIONALISM: A POLITICAL SOCIOLOGY OF THE CENTRAL AMERICAN INTEGRATION - Parthenay, Kevin (2016)
This article is part of a general study of the institutional evolution of the Central AmericanIntegration System (SICA ). It’s analyzed the changing roles and attitudes of regional actorsand, in such a perspective, the progressive establishment of a supranational civil servicein Central America. This paper of political sociology is based on field work, analysis ofarchives and more than 60 interviews.